2001
DOI: 10.1021/jp0116499
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo Simulations of Small Sulfuric Acid−Water Clusters

Abstract: Effective atom-atom potentials are developed for binary sulfuric acid-water clusters and applied in a Bennett Metropolis Monte Carlo calculation to determine free energy differences for small neighboring sized clusters of fixed composition at 298 K. The atom-atom pair potentials consist of Lennard-Jones short-range and Coulombic long-range terms and assume rigid SO 4 2δ-with two unconstrained H δ+ and rigid H 2 O molecules interacting via revised central force (RSL2) potentials. The potential parameters are de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 60 publications
1
22
0
Order By: Relevance
“…Hale et al [38][39][40] performed Monte Carlo simulations on the cluster energetics of water clusters, unary and binary LJ systems, and binary sulfuric acid-water. They found that when the differential Helmholtz energy, F n -F n-1 , is plotted versus n -1/3 [essentially n 2/3 -(n -1) 2/3 ], the data points fit well to a straight line down to n as small as 5-10, which suggests that even very small clusters already exhibit bulklike behavior.…”
Section: Dependence Of Interfacial Free Energy On Temperature and Sizementioning
confidence: 99%
“…Hale et al [38][39][40] performed Monte Carlo simulations on the cluster energetics of water clusters, unary and binary LJ systems, and binary sulfuric acid-water. They found that when the differential Helmholtz energy, F n -F n-1 , is plotted versus n -1/3 [essentially n 2/3 -(n -1) 2/3 ], the data points fit well to a straight line down to n as small as 5-10, which suggests that even very small clusters already exhibit bulklike behavior.…”
Section: Dependence Of Interfacial Free Energy On Temperature and Sizementioning
confidence: 99%
“…Values of -δf n are determined after equilibration from Monte Carlo runs of length 30 to 50 million steps, using different initial configurations. The values of -δf n are also generated from two independently developed codes, one of which was used for binary clusters 61 and moved all of the molecules at each step.…”
Section: Small Cluster Bennett Monte Carlo Free Energy Differencmentioning
confidence: 99%
“…Thus liquid drop models describe them very inaccurately. Classical simulations [ Kathman and Hale , 2001; Kusaka et al , 1998] capture the true nature of newly formed particles as molecular clusters, but suffer from the lack of transferable interaction potentials able to describe correctly the various binding states of, for example, water and sulfuric acid. Quantum chemical methods are needed to understand properties of these clusters, where proton transfer is an essential part of bond formation.…”
Section: Introductionmentioning
confidence: 99%